General factors affecting drug metabolism: the role of nuclear receptor superfamily members in induction - Maurel, Patrick (Henry Stewart Talks, 2007)
Drug metabolism and gene transcription, Role of nuclear receptors in drug metabolism induction, Aryl hydrocarbon receptor, Pregnane X receptor, Constitutive androstane receptor, Human examples of drug metabolism induction
Archived at 2015/09/24